ONSANSE’S LANGUAGE: NOT MORE THAN TWO-WORD UTTERANCES AFTER FORTY YEARS OF EXPOSURE TO FOUR LANGUAGES (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper set out to investigate the amount and nature of language thesubject of the study (Onsanse) has learnt for four decades of exposure toseveral languages after being picked up at the age of 17, when he couldproduce only one word and one interjection in Ekegusii. The data fromconversations and observations audio- and video-recorded for 154 hoursshow that Onsanse has picked up an amount of vocabulary that enableshim to interact with people especially in Dholuo and Kiswahili. However,he has not acquired a grammar that would enable him to produce anutterance longer than two words. In another respect Onsanse’s grammaris comparable to that of Specific Language Impairment subjects, sinceits morphological component is selectively impaired: for instance, inDholuo, the language he seems to be most “competent” in, Onsanse hasgreater difficulty in using the singular subject marker prefix than itsplural counterpart. At the phonological level, his speech was marked byomissions and substitutions of phonemes, but no typical features stoodout as typical of his speech.